Church development perspective policy formulation and implementation - Genato-Rebullida, Ma. Lourdes (Philippine Journal of Public Administration, 1991)
Culled largely from the explicit pronouncements and actual practices of the churches for the period covering 1972-1990, this article is an attempt to piece together the church sector's development perspective using the policy formulation and implementation framework. The record of the performance of the Catholic Church and the Protestant member-churches of the National Council of Churches in the Philippines indicates the potential of historic social institutions, religious belief systems, and churches as organizations in the continuing task of accomplishing the much desired progress and development of Filipino society.